Meningkatkan Kesejahteraan Subjektif Penderita Penyakit Jantung Melalui Pelatihan Kebersyukuran - Ririn Nur Abdiah Bahar; Moordiningsih Moordiningsih (Faculty of Ushuluddin and Humanities, 2020)
Individuals diagnosed with heart disease, especially at young people will cause psychological burden because they have to do long-term treatment, even last a lifetime with various risks that accompany, so that it will reduce subjective well-being for sufferers. The hypothesis of this study is subjective well-being of people with heart disease increases after receiving Gratitude Training. This study uses one group pretest-posttest with follow-up design. The measurement of subjective well-being is done by using SWLS and PANAS in Indonesian version. Gratitude training is given to individuals diagnosed with heart disease at productive age, 20-45 years (n = 5). Subjects attended the Gratitude Training 2 times online meetings. The analysis used in this study, the Friedman Test which showed significant results (χr2 = 8.4; p <0.05). These results indicate that the Gratitude Training in this study was proven to improve subjective well-being in people with heart disease.